Influence of Device Design Parameters on Static and Dynamic Performances of Trench Gate IGBT - Luther Ngwendson (Kongzhi Yu Xinxi Jishu)
Significant progress has been made by combining trench gate cell design and field stop (or SPT) buffer concept in modern IGBT technology. In this paper, we explored the different device design parameters that could be optimised to obtain best-in-class static and dynamic performance of trench gate IGBT in particular. This includes parameters such as active and dummy trench cell design, carrier injection enhancement, soft punch through, etc. It is shown that the parameter combination for optimisation will change depending on application needs such as low on-state voltage drop, low turn-off energy loss or ruggedness in terms of RBSOA and SCSOA. Additionally we investigated the design parameters necessary for best performance in low inductance circuits which are important in HEV/EV applications.